Monocrystal sodium ferric sulfate composite electrode material and preparation method thereof

The preparation of single-crystal sodium ferrosulfate composite flash graphene electrode material through physical ball milling and low-temperature solid-phase calcination method has solved the problems of low circulation performance and poor conductivity of the existing sodium ferrosulfate materials, and achieved high circulation stability and conductivity of the material.

CN119542399APending Publication Date: 2025-02-28SHANXI UNIV

Patent Information

Application Number
CN202411740062.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing sodium ferric sulfate materials have low cycling performance and poor conductivity, which is mainly due to their polycrystalline structure that causes stress and microcracks to occur during the charge and discharge process, affecting the stability of the material.

Method used

The electrode material of single-crystalline iron sulfate composite flash graphene is prepared by using physical ball milling and low-temperature solid-phase calcining method. Through the lubrication and grinding of flash graphene, the crystal phase purity and conductivity of sodium iron sulfate are improved.

Benefits of technology

The excellent cycle stability and rate performance of the single-crystal sodium iron sulfate composite electrode material has been achieved. The capacity retention rate of the material reaches more than 96% after 5,000 cycles, and has strong market competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542399A_ABST
    Figure CN119542399A_ABST
Patent Text Reader

Abstract

The invention discloses a monocrystal sodium ferric sulfate composite electrode material and a preparation method thereof, and belongs to the technical field of sodium ion battery positive electrode materials. Aiming at the problems of low cycle performance and poor conductivity of the current sodium ferric sulfate material, ferrous sulfate heptahydrate is roasted in an inert atmosphere to obtain anhydrous ferrous sulfate (FeSO4). 2, carrying out ball milling, crushing and mixing on anhydrous FeSO4, anhydrous Na2SO4 and the flash graphene according to a certain mass ratio to obtain a mixed precursor; and 3, sintering the roasted precursor material in a rotary tube furnace protected by an inert atmosphere to obtain the single-crystal sodium ferric sulfate composite positive electrode material. According to the preparation method disclosed by the invention, the mixing uniformity of the two raw materials in a quasi-nano scale is improved based on the lubricating and grinding-aiding effects of the flash graphene on a material precursor, and meanwhile, the growth uniformity of the sodium ferric sulfate crystal can be effectively promoted by combining the precise proportion design of FeSO4 and Na2SO4, so that the material with a pure-phase single-crystal structure and excellent sodium storage cycle performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to a single crystal sodium iron sulfate composite electrode material and a preparation method thereof. Background Art

[0002] Due to the intermittent and volatile nature of renewable energy sources such as solar and wind power, the development of large-scale energy storage systems has become key to the development of the new energy industry. In current energy storage systems, sodium-ion batteries (SIBs) have become one of the most promising options due to their abundant sodium resources, low cost and high safety. Among them, the cathode material, as the core component of SIBs, has a decisive influence on the performance and cost of the entire battery system. Therefore, cathode materials with high capacity, high stability and low cost are crucial for the widespread application of SIBs.

[0003] At present, sodium ferric sulfate, an iron-based polyanion compound with a three-dimensional stable framework structure, has attracted great attention due to its abundant iron raw materials, low cost, open sodium ion conduction path and an average operating voltage of up to 3.8V. However, the synthesis of high-performance sodium ferric sulfate materials is relatively difficult and has obvious defects such as impure crystal phase and poor conductivity.

[0004] Recent studies have mainly solved the above problems by improving the synthesis method and compounding with highly conductive carbon materials. The synthesized composite material has a good sodium storage capacity (CN 118117067 A, CN 114267838A, Nature Communications, 2023, 14: 3701), but the long-term cycle performance of the material is still not ideal. The main reason is that the currently synthesized sodium iron sulfate material is a polycrystalline structure, composed of nanoscale primary crystal particles, and there are a large number of grain boundaries between the primary particles. During the charge and discharge process, the non-uniform volume changes between these particles will produce large stresses and cause a large number of microcracks in the particles along the grain boundaries. These microcracks are exposed to the electrolyte and induce additional side reactions, thereby causing the material performance to deteriorate during the cycle. Summary of the invention

[0005] In view of the problems of low cycle performance and poor conductivity of the current sodium ferric sulfate material, the present invention provides a method for preparing a single-crystal sodium ferric sulfate composite electrode material, adopts physical ball milling and low-temperature solid phase calcination methods to prepare the electrode material of single-crystal sodium ferric sulfate composite flash graphene, utilizes the lubrication and grinding aid effect of flash graphene to ensure the uniformity of the sodium ferric sulfate preparation precursor, and combines with a specific raw material ratio design to obtain a single-crystal composite electrode material with excellent cycle stability and rate performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A single-crystal sodium iron sulfate composite electrode material mainly comprises sodium iron sulfate single crystal particles and flash-evaporated graphene.

[0008] Furthermore, the mass ratio of the sodium ferric sulfate single crystal particles and the flash-evaporated graphene is: 90-97% of the sodium ferric sulfate single crystal particles and 3-10% of the flash-evaporated graphene.

[0009] Further, the chemical formula of the sodium ferric sulfate is: Na 2+2x Fe 2-x (SO4)3, where x ranges from 0.32 to 0.38.

[0010] Furthermore, the Joule heat treatment temperature of the flash graphene is between 3100 and 3300 K, and the time is less than 1 s.

[0011] A method for preparing a single crystal sodium iron sulfate composite electrode material comprises the following steps:

[0012] S1, subjecting ferrous sulfate heptahydrate to heat treatment in an inert atmosphere tube furnace to obtain anhydrous ferrous sulfate;

[0013] S2, ball milling anhydrous ferrous sulfate, anhydrous sodium sulfate and flash graphene in an inert atmosphere ball mill for 4 to 12 hours to obtain a calcined precursor;

[0014] S3, placing the calcined precursor in an inert atmosphere tube furnace at 350°C for calcination treatment, with a heating rate of 1.5-2°C / min and a calcination time of 6-15h to obtain a single crystal sodium iron sulfate composite electrode material.

[0015] Furthermore, in step 1, the heat treatment temperature is 250° C. and the time is 4 to 12 hours.

[0016] Furthermore, in the step 2, the gas filled in the inert atmosphere ball milling jar is argon, and the ball milling time is 4 to 12 hours.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] (1) By precisely adjusting the ratio of the raw materials ferrous sulfate and sodium sulfate, combined with the flash graphene turbo-layered graphene structure (with excellent thermal conductivity in multiple directions), the solid-phase reaction energy barrier can be reduced, and the initial formation of sodium ferric sulfate single crystal nuclei can be achieved during the ball milling stage. Based on the formation of these primary nuclei, the reaction raw materials can further grow around the nuclei to obtain micron-sized single crystal particles, greatly improving the purity of the sodium ferric sulfate crystal phase. At the same time, the flash graphene and sodium ferric sulfate single crystal particles are combined in the form of "quasi-chemical bonds", which can effectively improve the conductivity of the composite material.

[0019] (2) Unexpectedly, in order to prepare the composite material of the present invention, each node in the preparation method was precisely controlled, and it was found that the preparation method of the present invention is simpler and has lower cost than the conventional sodium iron sulfate composite electrode material, which makes the material have better cycle stability (>5000 times) and has stronger market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a charge and discharge curve diagram corresponding to the sodium ion battery prepared using the sodium iron sulfate composite positive electrode material obtained in Example 1 of the present invention.

[0021] Figure 2 This is a cycle performance diagram corresponding to the sodium ion battery prepared by the sodium iron sulfate composite positive electrode material obtained in Example 2 of the present invention.

[0022] Figure 3 This is a rate performance diagram corresponding to the sodium ion battery prepared by the sodium iron sulfate composite positive electrode material obtained in Example 2 of the present invention.

[0023] Figure 4 This is the long cycle diagram corresponding to the sodium ion battery prepared by the sodium iron sulfate composite positive electrode material obtained in Example 2 of the present invention.

[0024] Figure 5 This is a scanning electron microscope image corresponding to the sodium iron sulfate composite positive electrode material obtained in Example 3 of the present invention.

[0025] Figure 6 This is a transmission electron micrograph of the sodium iron sulfate composite positive electrode material obtained in Example 3 of the present invention.

[0026] Figure 7 The XRD refinement diagram of the sodium iron sulfate composite positive electrode material obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0027] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.

[0028] Example 1

[0029] S1, heat-treat 91.18 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 4 h to obtain 49.86 g of anhydrous ferrous sulfate.

[0030] S2, 49.86 g of anhydrous ferrous sulfate, 38.62 g of anhydrous sodium sulfate and 2.74 g of flash graphene are ball-milled in an inert atmosphere ball mill for 9 h to obtain a calcined precursor.

[0031] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 350°C, with a heating rate of 1.8°C / min and a calcination time of 9h to obtain a single crystal sodium iron sulfate composite electrode material, wherein the molecular formula of the single crystal sodium iron sulfate is Na 2.72 Fe 1.64 (SO4)3, the flash graphene content is 3.00wt%.

[0032] The sodium iron sulfate composite positive electrode material is used to prepare a sodium ion battery. The charge and discharge curve of the sodium ion battery is shown in the figure below. Figure 1 As shown, the test results prove that the discharge capacity of the material can reach more than 100 mAh / g.

[0033] Example 2

[0034] S1, heat-treat 91.18 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 4 h to obtain 49.86 g of anhydrous ferrous sulfate.

[0035] S2, 49.86 g of anhydrous ferrous sulfate, 38.62 g of anhydrous sodium sulfate and 4.31 g of flash graphene are ball-milled in an inert atmosphere ball mill for 5 h to obtain a calcined precursor.

[0036] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 350°C, with a heating rate of 1.8°C / min and a calcination time of 9h to obtain a single crystal sodium iron sulfate composite electrode material, wherein the molecular formula of the single crystal sodium iron sulfate is Na 2.72 Fe 1.64 (SO4)3, the flash graphene content is 4.64wt%.

[0037] The sodium iron sulfate composite positive electrode material obtained above is used to prepare a sodium ion battery. The corresponding cycle performance diagram of the sodium ion battery is as follows: Figure 2 As shown, it proves that the material has good stability at 0.1C; the corresponding rate performance diagram of sodium ion battery is as follows Figure 3 As shown, the results show that the material still has a cycle capacity of nearly 80mAh / g at a large rate of 15C; the long cycle diagram corresponding to the sodium ion battery is shown in Figure 4 As shown, the results show that the capacity retention rate of the material reaches more than 96% after 5000 cycles, and it has excellent cycle stability.

[0038] Example 3

[0039] S1, heat-treat 46.72 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 6 h to obtain 25.54 g of anhydrous ferrous sulfate.

[0040] S2, 25.54 g of anhydrous ferrous sulfate, 18.75 g of anhydrous sodium sulfate and 2.45 g of flash graphene are ball-milled in an inert atmosphere ball mill for 4 h to obtain a calcined precursor.

[0041] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 350°C, with a heating rate of 1.5°C / min and a calcination time of 6h to obtain a single crystal sodium iron sulfate composite electrode material, wherein the molecular formula of the single crystal sodium iron sulfate is Na 2.64 Fe 1.68 (SO4)3, the flash graphene content is 5.24wt%.

[0042] The scanning electron microscope image corresponding to the above-mentioned single crystal sodium ferric sulfate composite electrode material clearly shows that the crystal growth of the single crystal sodium ferric sulfate is good and the crystal size is relatively uniform; the transmission electron microscope image of the sodium ferric sulfate composite positive electrode material shows the polyhedral structure of the sodium ferric sulfate single crystal, and the single crystal diffraction spots of the selected area electron diffraction confirm that it has a complete single crystal structure; the XRD refinement image of the sodium ferric sulfate composite positive electrode material shows the fitting degree: Rwp = 1.57%, which proves that the material has a good crystal form, high phase purity and low impurity content.

[0043] Example 4

[0044] S1, heat-treat 46.72 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 8 h to obtain 25.54 g of anhydrous ferrous sulfate.

[0045] S2, 25.54 g of anhydrous ferrous sulfate, 18.75 g of anhydrous sodium sulfate and 2.86 g of flash graphene are ball-milled in an inert atmosphere ball mill for 4 h to obtain a calcined precursor.

[0046] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 350°C, with a heating rate of 1.5°C / min and a calcination time of 6h to obtain a single crystal sodium iron sulfate composite electrode material, wherein the molecular formula of the single crystal sodium iron sulfate is Na 2.64 Fe 1.68 (SO4)3, the flash graphene content is 6.07wt%.

[0047] Example 5

[0048] 45.04 g of ferrous sulfate heptahydrate was heat treated at 250° C. in an inert atmosphere tube furnace for 12 h to obtain 24.63 g of anhydrous ferrous sulfate.

[0049] S2, 24.63 g of anhydrous ferrous sulfate, 19.60 g of anhydrous sodium sulfate and 4.91 g of flash graphene are ball-milled in an inert atmosphere ball mill for 12 h to obtain a calcined precursor.

[0050] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 350°C, with a heating rate of 2°C / min and a calcination time of 15h to obtain a single crystal sodium iron sulfate composite electrode material, wherein the molecular formula of the single crystal sodium iron sulfate is Na 2.76 Fe 1.62 (SO4)3, the flash graphene content is 9.99wt%.

[0051] Example 6

[0052] 45.04 g of ferrous sulfate heptahydrate was heat treated at 250° C. in an inert atmosphere tube furnace for 12 h to obtain 24.63 g of anhydrous ferrous sulfate.

[0053] S2, 24.63 g of anhydrous ferrous sulfate, 19.60 g of anhydrous sodium sulfate and 4.05 g of flash graphene are ball-milled in an inert atmosphere ball mill for 6 h to obtain a calcined precursor.

[0054] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 350°C, with a heating rate of 2°C / min and a calcination time of 12h to obtain a single crystal sodium iron sulfate composite electrode material, wherein the molecular formula of the single crystal sodium iron sulfate is Na 2.76 Fe 1.62 (SO4)3, the flash graphene content is 8.39wt%.

[0055] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

Claims

1. A single crystal sodium iron sulfate composite electrode material, characterized in that: The main components include sodium iron sulfate single crystal particles and flash graphene; the chemical formula of the sodium iron sulfate is: Na 2+2x Fe 2-x (SO4)3, where x ranges from 0.32 to 0.

38.

2. The single crystal sodium iron sulfate composite electrode material according to claim 1, characterized in that: The mass ratio of the sodium ferric sulfate single crystal particles and the flash-evaporated graphene is: 90-97% of the sodium ferric sulfate single crystal particles and 3-10% of the flash-evaporated graphene.

3. The single crystal sodium iron sulfate composite electrode material according to claim 1, characterized in that: The Joule heat treatment temperature of the flash graphene is between 3100 and 3300 K, and the time is less than 1 second.

4. The method for preparing a single crystal sodium iron sulfate composite electrode material according to claim 1, characterized in that: The following steps are involved: S1, subjecting ferrous sulfate heptahydrate to heat treatment in an inert atmosphere tube furnace to obtain anhydrous ferrous sulfate; S2, ball milling anhydrous ferrous sulfate, anhydrous sodium sulfate and flash graphene in an inert atmosphere ball mill for 4 to 12 hours to obtain a calcined precursor; S3, placing the calcined precursor in an inert atmosphere tube furnace at 350°C for calcination treatment, with a heating rate of 1.5-2°C / min and a calcination time of 6-15h to obtain a single crystal sodium iron sulfate composite electrode material.

5. The method for preparing a single crystal sodium iron sulfate composite electrode material according to claim 4 is characterized in that: In step 1, the heat treatment temperature is 250° C. and the time is 4 to 12 hours.

6. The method for preparing a single crystal sodium iron sulfate composite electrode material according to claim 4 is characterized in that: In the step 2, the gas filled in the inert atmosphere ball milling jar is argon, and the ball milling time is 4 to 12 hours.

Citation Information

Patent Citations

  • Flash graphene coated sodium ferric sulfate composite electrode material and preparation method thereof

    CN117613248A

Cited By

  • Preparation method of high-rate-performance sodium ferric sulfate positive electrode material, positive electrode material, electrode plate and sodium ion battery

    CN122158670A